Sistem Manajemen Sanggar Seni Lubuak Nan Tigo Kota Solok - Bunga Lovesky; Indrayuda Indrayuda (Universitas Palangka Raya, 2024)
This article aims to explain and describe the Management System of Lubuak Nan Tigo Art Studio Solok City. This type of research is qualitative research with descriptive methods. This research instrument is its own research and is assisted by supporting instruments such as stationery, cameras and flash drives. This research data uses primary data and secondary data. Data were collected through literature study, observation, interviews and documentation. The steps of analyzing data are data reduction, data presentation and conclusions. The results of this study show that Lubuak Nan Tigo Art Studio runs a democratic management system, cooperation, cohesiveness and seriousness in carrying out duties. The management functions used are planning, organizing, actuating, supervision. Which for the achievement of a good management system requires cooperation, seriousness and cohesion from the members. If one of the management processes does not work, then the results will not be as expected. With the provision of motivation and input from the studio leadership, all members in charge of carrying out their respective duties responsibly, thus making the management system of Lubuak Nan Tigo Art Studio run well and be able to dominate the entertainment land industry market, especially in Solok City.